Computer science teacher : insight into the computing classroom - Clarke, Beverly (BCS, The Chartered Institute for IT, 2017)
Increased focus on computer science has recently brought about the new national curriculum in computing. It is the role of the Computer Science Teacher to not only understand the curriculum and subject inside out and teach it to their classes but also to influence their pupils perceptions of computing and how it will shape their futures. This book explores the role of Computer Science Teacher in a secondary school environment. An overview of secondary school computing is covered, along with what the role encompasses, the attributes, knowledge and skills required to be a success and useful standards, tools, methods and techniques you can employ. Case studies and quotes from schools and current teachers are also included.